2008
DOI: 10.1111/j.1365-2486.2008.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in circumpolar seabird populations linked to climate oscillations

Abstract: We found that synchronous fluctuations of two congeneric seabird species across the entire Arctic and sub-Arctic regions were associated with changes in sea surface temperatures (SST) that were linked to two climate shifts, in 1977 and again in 1989. As the SST changes linked to climate shifts were congruent at the scale of ocean basins, fluctuations of these species occurred similarly at continental or basin scale. Changes in colony sizes were examined for a decade following climate shifts. The magnitude of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 33 publications
3
77
0
Order By: Relevance
“…In the former case, researchers assume that those covariates influence mainly fertility and the effects on population numbers are reflected some years later, owing that seabirds do not reach sexual maturity for several years until recruitment (Cook et al, 2014). In some other cases, climate covariates of the previous year were tested, and researchers assume that conditions prior to breeding were more important by influencing adult survival, breeding propensity and immigration (Jenouvrier et al, 2003;Frederiksen et al, 2008;Irons et al, 2008;Devney et al, 2009;Lauria et al, 2012). The absence of time lag in the response of seabirds to climate variability may be reasonable in some situations, even when the process invoked is food availability, because availability of food depends on its abundance, accessibility, and distribution, which can be directly influenced by climate.…”
Section: The Mechanisms Linking Climate Variation To Seabird Populatimentioning
confidence: 99%
“…In the former case, researchers assume that those covariates influence mainly fertility and the effects on population numbers are reflected some years later, owing that seabirds do not reach sexual maturity for several years until recruitment (Cook et al, 2014). In some other cases, climate covariates of the previous year were tested, and researchers assume that conditions prior to breeding were more important by influencing adult survival, breeding propensity and immigration (Jenouvrier et al, 2003;Frederiksen et al, 2008;Irons et al, 2008;Devney et al, 2009;Lauria et al, 2012). The absence of time lag in the response of seabirds to climate variability may be reasonable in some situations, even when the process invoked is food availability, because availability of food depends on its abundance, accessibility, and distribution, which can be directly influenced by climate.…”
Section: The Mechanisms Linking Climate Variation To Seabird Populatimentioning
confidence: 99%
“…Climate-in duced environmental changes may influence the timing and magnitude of these peaks (Mackas et al 2007, Hunt et al 2008. However, specific effects of environmental changes on seabirds vary across re gions (Irons et al 2008). In particular, the mechanisms underlying physical forcing are thought to be fundamentally different in marine ecosystems with seasonal ice cover (Hunt et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A study of five seabird species at Hornøya in the Barents Sea showed generally weak negative relationships between adult survival and sea temperature, and interpreted these as indirect climate effects mediated through prey abundance, possibly in the wintering areas (Sandvik et al 2005). In a circumpolar study, Irons et al (2008) found that colonies of both common and Brünnich's guillemots tended to decrease following major changes (increases or decreases) in sea temperature, whereas they increased or remained stable when temperatures showed little change. Again, these findings are more consistent with indirect trophic effects of climate than with a direct physiological impact.…”
Section: Indirect Effects Of Climatementioning
confidence: 99%